Case study as an investigative path in Education research (Research, Society and Development, 2022)
In this work we present a summary of the Case Study and its applicability in research in the area of education. It is a bibliographic mapping that was carried out during the Master's Course in Education at the Federal University of Amazonas (UFAM). For thematic reflection, we also take into consideration the dialogues coming from the Group of Studies and Research of Investigative Practices in Mathematical Education (GEPIMat)/UFAM. Starting from this premise, we aim to present the characterization and applicability of the Case Study in Education research, specifically in Mathematics Education to investigate questions related to the continuing education of teachers who teach mathematics. Likewise, we seek to know: What is a Case Study and its applicability in research in Mathematics Education? For this, we carried out a bibliographical survey regarding the authors who elucidated the Case Study as a means to seek answers to research focused on the area of education. As a result of this survey, we highlight the theoretical contributions of Yin (2015), Ponte (2006) among others. We conclude that the information collected in this study can contribute to researchers in the Education area who intend to use this methodology in their research, particularly those focused on Mathematics Education.